Resposta imune humoral em bovinos induzida pela glicoproteína D recombinante de herpesvírus bovino tipo 5 - Araujo, Itauá Leston (2014)
Glycoprotein D (gD) is essential for attachment and penetration of bovine herpesvirus type 5 (BoHV-5) into susceptible cells, and is a major target of host immune systems, inducing strong humoral and cellular immune responses. The immunogenicity of recombinant BoHV-5 (rgD5) expressed in Pichia pastoris was evaluated in bovines. Vaccines formulated with 100 μg rgD5 dose and adjuvants (Montanide ISA50V2 or Aluminum Hydroxide) with or without inactivated BoHV-5 or rgD5 without adjuvants were administered intramuscularly. A commercial vaccine was also used as control. The vaccine formulation rgD5 + ISA50V2 stimulated humoral immune responses after two doses, and higher titer of neutralizing antibodies were obtained in all three oil-based adjuvants formulations when compared to Hydroxide Aluminium adjuvant or the commercial vaccine. The vaccine BoHV-5 + rgD5 + ISA50V2 stimulated titers of neutralizing antibodies approximately 8 log2, which demonstrated higher correlations on the Indirect ELISA. Together, the results suggest that the recombinant gD5 conserved neutralizing epitopes and was able to stimulate a efficient humoral immune response in bovines.